The Interrogator's War : Inside the Secret War Against Al Qaeda - Mackey, Chris and Miller, Greg (GHQ, Rawalpindi Army Education Publishing House, 2006)
The methods of the US military in conducting the War on Terror have recently come under intense international scrutiny and criticism. But there is much that remains unclear about the realities on the ground, in those cramped cells in the midst of combat zones where terrorist suspects come head-to-head with trained interrogators. Now, for the first time, the inside story of this secret war is uncovered by Chris Mackey, a senior US Army interrogator in Afghanistan, who interviewed thousands of Al Qaeda and Taliban suspects, many of whom he sent to Guantanamo Bay. In Afghanistan the interrogators faced an enemy who, with tactics like sleeper cells and suicide bombers, were unlike any other they had seen. Working round the clock, Mackey and his team had to discard outmoded Cold War interrogation techniques and evolve breakthrough psychological strategies and complex mind games. But the interrogators too were under immense pressure; relentlessly pitching their wits against suspected fanatics, ever fearful that their prisoners might know of another 9/11, but constrained from unleashing their tempers by the Geneva Convention, it was not always just the prisoners who cracked.Mackey's compelling picture of the exhausting interrogations and pressure-cooker atmosphere which built up under the relentless Afghan sun gives a troubling insight into the temptations and obstacles in the path of sound military judgement. But it is also a testament to the strength of character of those many interrogators who remained professional, rational and played by the rules.
Include Appendix, Epilogue and Map.
Keywords: Afghan War, 2001- -- Military Intelligence -- Afghan War, 2001- -- Prisoners and Prisons, American